Healthcare use and expenditure for diabetes in Bangladesh. Issue 1 (3rd January 2017) - Shariful Islam, Sheikh Mohammed; Lechner, Andreas; Ferrari, Uta; Laxy, Michael; Seissler, Jochen; Brown, Jonathan; Niessen, Louis W; Holle, Rolf
Abstract : Background: Diabetes imposes a huge social and economic impact on nations. However, information on the costs of treating and managing diabetes in developing countries is limited. The aim of this study was to estimate healthcare use and expenditure for diabetes in Bangladesh. Methods: We conducted a matched case–control study between January and July 2014 among 591 adults with diagnosed diabetes mellitus (DMs) and 591 age-matched, sex-matched and residence-matched persons without diabetes mellitus (non-DMs). We recruited DMs from consecutive patients and non-DMs from accompanying persons in the Bangladesh Institute of Health Science (BIHS) hospital in Dhaka, Bangladesh. We estimated the impact of diabetes on healthcare use and expenditure by calculating ratios and differences between DMs and non-DMs for all expenses related to healthcare use and tested for statistical difference using Student's t-tests. Results: DMs had two times more days of inpatient treatment, 1.3 times more outpatient visits, and 9.7 times more medications than non-DMs (all p<0.005). The total annual per capita expenditure on medical care was 6.1 times higher for DMs than non-DMs (US635 vs US104, respectively). Among DMs, 9.8% reported not taking any antidiabetic medications, 46.4% took metformin, 38.7% sulfonylurea, 40.8% insulin, 38.7% any antihypertensive medication, and 14.2% took anti-lipids over the preceding 3 months. Conclusions: Diabetes significantly increases healthcare use and expenditure and is likely to impose a huge economic burden on the healthcare systems in Bangladesh. The study highlights the importance of prevention and optimum management of diabetes in Bangladesh and other developing countries, to gain a strong economic incentive through implementing multisectoral approach and cost-effective prevention strategies.